Dinâmica populacional e manejo de pragas nas culturas de arroz, milho e soja no cerrado de Roraima - Negrini, Marcelo (2019)
Agricultural activity in Roraima has been increasing in recent years, with rice, soybean and corn crops making up most of the state's annual crop areas. In this sense, knowledge about the composition of species associated to these crops, their population dynamics and management methods are scarce in Roraima. The objective of this thesis was to evaluate the population dynamics of insects and mites pests and their natural enemies in irrigated rice, corn and soybean crops in Roraima, determine methods of management of Spodoptera frugiperda and map out the risk of establishment of the panicle rice mite, Steneotarsonemus spinki in Brazil. Insects and mites were sampled in areas of soybean, corn and rice farming. In addition, tests were performed with alternative methods of handling S. frugiperda with entomopathogenic fungi and essential oils. Using the MaxEnt, the risk of entry and establishment of S. spinki in rice crops was determined. In soybean the caterpillar pests are Chrysodeixis includens, Anticarsia gemmatalis, Helicoverpa sp. S. cosmioides and S. frugiperda, whereas in the cultivation of Bt maize we have S. frugiperda, S. albula, S. cosmioides and Helicoverpa zea. As natural enemies the parasitoids Glyptapanteles hebertii, Chalcididae, Winthemia sp. and Chetogena cf sp. and the entomopathogenic fungus Metarhizium sp. In the cultivation of irrigated rice the main pests were Argyria sp., Oebalus poecilus, Marasmia trapezalis, Panoquina sp., S. frugiperda, Tibraca limbativentris and Rupela albinella. Among the rice mites are the genera of predatory species Lasioseius spp. Neoseiulus spp. and Pseudoparasitus spp. Among the management methods for S. frugiperda no efficient bioprospecting fungal isolate was obtained, however the commercial fungus based on Beauveria bassiana provided 86.7% mortality rates at 107 conidia / mL and essential oils of Corymbia citriodora and Lippia microphylla were efficient in topical and volatile applications. According to the model generated in MaxEnt it was verified that there is a high risk of establishment of S. spinki in rice crops in Roraima to the producing regions of southern Brazil. Despite the incidence of pests, a number of natural enemies are observed in the studied areas, even with insecticide-intensive use.